2007
DOI: 10.1097/qad.0b013e3280118fca
|View full text |Cite
|
Sign up to set email alerts
|

Elevated risk of lung cancer among people with AIDS

Abstract: Lung cancer risk was substantially elevated among PWA. Smoking could not entirely account for the observed elevation, especially among younger adults, suggesting a role for additional co-factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
140
2
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(155 citation statements)
references
References 25 publications
10
140
2
3
Order By: Relevance
“…14,15 The incidence of NSCLC also is increased after organ transplantation and in patients with acquired immunodeficiency syndrome. 16,17 Tumor-infiltrating lymphocytes are considered an indication of the host-immune reaction to tumor antigens, and we demonstrated previously that high tumor-related stromal CD4 and CD8 expression is strongly associated with a good prognosis. 10 To our knowledge, this is the first study to report that the combination of low adaptive stromal immunity and high tumor cell expression of angiogenic markers has a substantial and independent, negative impact on patients with lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 The incidence of NSCLC also is increased after organ transplantation and in patients with acquired immunodeficiency syndrome. 16,17 Tumor-infiltrating lymphocytes are considered an indication of the host-immune reaction to tumor antigens, and we demonstrated previously that high tumor-related stromal CD4 and CD8 expression is strongly associated with a good prognosis. 10 To our knowledge, this is the first study to report that the combination of low adaptive stromal immunity and high tumor cell expression of angiogenic markers has a substantial and independent, negative impact on patients with lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies comprised only of AIDS patients appear to have similar risks for lung cancer associated with HIV as do studies with representation across HIV disease stage (data not shown). Data from the large US AIDS-Cancer Registry Match indicated increased lung cancer risk among persons with AIDS but no significant association with CD41 cell counts (50,51). Some data have suggested that rates and mortality due to lung cancer and other tobacco-related disease have only increased among HIV-infected populations since the availability of combination ART (52).…”
Section: Role Of Immunosuppression Hiv Viral Load and Artmentioning
confidence: 99%
“…17 Since then, a number of studies carried out either exclusively before the HAART era or both before and during the HAART era have suggested that lung cancer risk is greater among HIV-infected individuals compared to the general population (Table 1). 11,12,[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] Though some of the largest studies included only patients with an AIDS-defining diagnosis 11,18,21,22 several cohort and registry linkage studies, which have included HIV-positive patients with and without AIDS, have also consistently demonstrated an increased risk of lung cancer. 19,23,27,[28][29][30]33 In a meta-analysis of seven reports of HIV-associated cancer risk and published between 2002 and 2006, 444,172 people with HIV/AIDS were identified, of whom 1,297 were diagnosed with lung cancer.…”
Section: Epidemiologymentioning
confidence: 99%
“…8.10,11 In this article, we will briefly review the emerging epidemiologic data that suggests that lung cancer risk is 2-4 times greater in HIV-infected persons than in the general population, even after adjusting for other factors such as smoking intensity and duration. [12][13][14][15][16] We will also review reasons why the risk of lung cancer may be greater in this group than the general population, then focus on clinical features of the disease, treatment recommendations and cigarette smoking prevention.…”
Section: Introductionmentioning
confidence: 99%